2006
DOI: 10.1016/j.nuclphysb.2006.05.012
|View full text |Cite
|
Sign up to set email alerts
|

D-string fluid in conifold: II. Matrix model for D-droplets on and

Abstract: Motivated by similarities between Fractional Quantum Hall (FQH) systems and aspects of topological string theory on conifold, we continue in the present paper our previous study (hep-th/0604001, hep-th/0601020) concerning FQH droplets on conifold. Here we focus our attention on the conifold sub-varieties S 3 and S 2 and study the non commutative quantum dynamics of D1 branes wrapped on a circle.We give a matrix model proposal for FQH droplets of N point like particles on S 3 and S 2 with filling fraction ν = 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…This may be done by extending the results of [13,14] obtained in the framework of fractional quantum Hall droplets. An attempt using matrix field variables valued in GL (N, C) representations is under study in [15], progress in this direction will be reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be done by extending the results of [13,14] obtained in the framework of fractional quantum Hall droplets. An attempt using matrix field variables valued in GL (N, C) representations is under study in [15], progress in this direction will be reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…We will give a brief comment on this method in the end of this section. More involved details may be found in [15].…”
Section: Holomorphy and Quantum Correctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While standard Chern-Simons (CS) gauge theories are topological theories involving hermitian gauge fields in odd spacetime [6], the Costello-Witten Yamazaki (CWY) theory lives in 4D space and goes beyond the hermiticity property. This non unitary feature allowed to extend the application of methods of standard QFT to complexified gauge fields living on complex manifolds [1,2,8,9,10]. The 4D-CS theory gives a new approach to describe major elements and phenomena of 2D integrable systems in terms of a complex CS gauge potential living on Σ × C and valued in a complex Lie algebra.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we use TBM to engineer a board class of lattice QFTs that are based on ADE Lie algebras [21,22] and their basic representations [23,24]. These engineered lattice systems classify the electronic properties of acetylene chain as a su (2) model, graphene as a su (3) lattice model and may have application in other fields; in particular in QFT on non commutative geometry [25,26,27], where space time is viewed as a crystal, and in the special subset of conformal field models based on affine Kac-Moody invariance and vertex operators [28,29,30]. To fix the ideas; let us describe briefly the main lines of the construction in the case of the series A N −1 ≃ su (N) [31] which is generated by (N − 1) commuting Cartan generators h i and N (N − 1) step operators E ±β where the vectors β = β 1 , ..., β N −1 stand for the positive roots of su (N).…”
Section: Introductionmentioning
confidence: 99%